Short-term Haematological Parameters Following Surgical Removal of Mandibular Third Molars with Different Doses of Methylprednisolone Compared with Placebo. A Randomized Controlled Trial - Marie Kjærgaard Larsen; Thomas Kofod; Kirsten Duch; Thomas Starch-Jensen (eJournal of Oral Maxillofacial Research)
Objectives: To evaluate the influence of a single intraoperative injection of methylprednisolone on short-term haematological parameters following surgical removal of mandibular third molars.